Pembangunan Sistem Informasi E-Voting Pada Universitas XYZ - Muhammad Nur Syamsudin; Yuyun Tri Wiranti; M. Ihsan Alfani Putera (LPPM STIKOM Tunas Bangsa, 2022)
An organization is a group of people who have a common goal, where everyone has the same goals so that they are combined and are expected to achieve goals together. The organization itself has a membership structure that functions to divide the tasks of each individual and each organization has a leader who functions to regulate the running of the organization. At XYZ University, there are various organizations that all students can participate in. The head of the organization is chosen from the election activities held every year to continue the baton of management. There are several obstacles experienced when conducting election activities, namely, election activities are carried out offline, due to pandemic conditions so that election activities cannot be carried out, there are many invalid ballots, and also the vote-counting process which takes quite a long time. In addition to obstacles during the election, election activities also cost quite a lot to print ballots and so on to launch elections. Therefore, this research was conducted by building an e-voting information system. The e-voting system itself has several advantages compared to elections conducted offline. It is hoped that the e-voting system can reduce errors made in offline elections. The system development uses the Personal Extreme Programming (PXP) method using the Laravel framework. It is hoped that the system built can assist the voting process in election activities at the XYZ University.